Reimagining the youth sport system aross the United States: A commentary from the 2020-2021 President`s Council on Sports, Fitness & Nutrition Science Board - Whitley, M. A.; Smith, A. L.; Dorsch, T. E.; Bowers, M. T.; Centeio, E. E. (Journal of Physical Education, Recreation & Dance, 2021)
The youth sport system in the United States is not achieving its full potential. There is a need to reimagine this system in ways that are evidence-based, innovative, and coordinated to best safeguard and promote the well-being of young people. The purpose of this expert commentary, composed by the President`s Council on Sports, Fitness & Nutrition Science Board, is to propose a set of changes across multiple levels of influence (e.g., individual, family, school, organization) that could cultivate a more developmentally sound youth sport system. By advancing the vision of the National Youth Sports Strategy to provide quality youth sport to all young people in the country, these changes have substantial potential to benefit young people.